2013
DOI: 10.1007/s00464-012-2697-2
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing working-space in laparoscopy: measuring the effect of mechanical bowel preparation in a porcine model

Abstract: Background Adequate working space is a prerequisite for safe and efficient minimal access surgery. No objective data exist in literature about the effect of mechanical bowel preparation (MBP) on working space in laparoscopic surgery. We objectively measured this effect with computed tomography in a porcine laparoscopy model. Methods Using standardized anesthesia, twelve 20-kg pigs without MBP and eight 20-kg pigs with MBP were studied with computed tomography at intra-abdominal pressure (IAP) levels of 0, 5, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 48 publications
(39 reference statements)
1
7
0
Order By: Relevance
“…Watkins et al used computed tomography to manually assess thoracic and abdominal volumes created by positive pressure insufflation as well as mechanical lift in dogs. Vlot et al reported pneumoperitoneum volume measurements using CT scans in porcine models, similar to that presented here. Porcine models were investigated during insufflation to define the contributions of subject, anesthetic, and pneumoperitoneum related factors.…”
Section: Discussionsupporting
confidence: 82%
“…Watkins et al used computed tomography to manually assess thoracic and abdominal volumes created by positive pressure insufflation as well as mechanical lift in dogs. Vlot et al reported pneumoperitoneum volume measurements using CT scans in porcine models, similar to that presented here. Porcine models were investigated during insufflation to define the contributions of subject, anesthetic, and pneumoperitoneum related factors.…”
Section: Discussionsupporting
confidence: 82%
“…Would MPB result in less impacted bowel and hence better handling? The use of MBP might improve the operative space by cleansing the bowel content [13] . A randomized control trial showed better surgical view in patients with MBP undergoing laparoscopic operations [14] .…”
Section: Discussionmentioning
confidence: 99%
“…Adequate working space is a prerequisite for safe and efficient minimal access surgery. [ 4 ] Several factors influence working space, for example, age and size of the patient, obesity, bowel content, pneumoperitoneum pressure, positioning of the patient, use of systemic neuromuscular blocking agents and ventilation settings. [ 5 ] The working space in infants is limited due to a combination of various factors such as small body habitus, relatively large size of liver and spleen and shallow pelvis.…”
Section: Discussionmentioning
confidence: 99%